Construction and characterization of the full-length cDNA of an infectious clone of emerging porcine teschovirus-2. Issue 1 (31st August 2022) - Li, Yuying; Chen, Shengnan; Shi, Yaokai; Huang, Haixin; Wang, Wei; Zheng, Min; Zhao, Chenchen; Zhang, Xinyu; Lei, Xiaoxiao; Sun, Wenchao; Liu, Hao; Lan, Tian
Abstract: Porcine teschovirus (PTV) is a causative agent of polioencephalomyelitis, encephalomyelitis, reproductive disorders and gastrointestinal and respiratory diseases in swine. In the present study, the PTV2 GX/2020 strain was isolated from pig intestinal tissue through the use of ST cells. Phylogenetic analysis of VP1 nucleotide sequences indicated that the GX/2020 isolate is closely related to PTV2. Furthermore, the full-length cDNA of an infectious GX/2020 clone was constructed using seamless ligation technology. The genome sequence of the rescued virus is largely consistent with the sequence of the parental virus, and it exhibits viral growth properties. The PTV2 virus was successfully isolated in the present study, and the reverse-genetic platform provides a foundation for studies of the pathogenic mechanisms of porcine teschovirus. Abstract : In order to further understand the Porcine teschovirus (PTV) genotype and virus characteristics, the authors successfully isolated the PTV-2 virus and established a reverse genetics system for the emerging PTV-2 GX/2020 isolate. They then demonstrated that a full-length cDNA clone (PTV-2 GX/2020) was able to replicate and infect ST cells.